Calvary [videorecording (DVD)] - McDonagh, John Michael; Gleeson, Brendan; O'Dowd, Chris, 1980-; Reilly, Kelly
Calvary's Father James is a good priest who is faced with sinister and troubling circumstances brought about by a mysterious member of his parish. Although he continues to comfort his own fragile daughter and reach out to help members of his church with their various scurrilous moral, and often comic, problems, he feels sinister and troubling forces closing in, and begins to wonder if he will have the courage to face his own personal Calvary.